Do differences matter? A typology of emerging adult romantic relationship. (May 2017) - Roberson, Patricia N. E.; Norona, Jerika Christine; Fish, Jessica N.; Olmstead, Spencer B.; Fincham, Frank
Romantic relationships among emerging adults (individuals aged 18–25 years) are typically homogenously classified both theoretically and empirically as "exploratory" and "unstable." With a sample of college students ( N = 340), we examined within-group variation among romantic relationships in emerging adulthood using latent class analyses. Four predictor variables indicated four types of romantic relationships among emerging adult college students: the committers (38%), the casual daters (23%), the settlers (30%), and the volatile daters (8%). Classes varied according to background variables such as gender and infidelity. Additionally, there was class variation for outcome variables such as breakup status and loneliness. Future research and implications are discussed.